2006
DOI: 10.1103/physrevlett.97.170402
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Difference in the Casimir Force for Samples with Different Charge-Carrier Densities

Abstract: A measurement of the Casimir force between a gold coated sphere and two Si plates of different carrier densities is performed using a high vacuum based atomic force microscope. The results are compared with the Lifshitz theory and good agreement is found. Our experiment demonstrates that by changing the carrier density of the semiconductor plate by several orders of magnitude it is possible to modify the Casimir interaction. This result may find applications in nanotechnology. PACS numbers: 12.20.Fv, 12.20.Ds,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 24 publications
3
159
1
Order By: Relevance
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…First, we briefly consider the preparation of the sphere which was done similar to previous experiments. [20][21][22]27,28,39,40,43,44 We used a polystyrene sphere which was glued with silver epoxy (20 × 20 µm 2 spot) to the tip of a triangular silicon nitride cantilever with a nominal spring constant of order 0.01 N/m. The cantilever-sphere system was then coated with a 10 nm Cr layer followed by 20 nm Al layer and finally with a 105 ± 1 nm Au layer.…”
Section: B Sample Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…2,5 Independent on separation contact potential was also reported in experiments by U. Mohideen. 2,4,5,[23][24][25] It is notable that all these experiments were performed in high vacuum with small spheres of order 100 µm curvature radii.…”
Section: Anomalies In Electrostatic Calibrationsmentioning
confidence: 99%